Dynamics of Diffusion and Mechanical Waves Interaction under Conditions of Metal Surface Treatment with Particle Fluxes; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Parfenova E. S. Elena Sergeevna (Simulation of Physical and Chemical Processes, 2014)
Title screen